Interfacial Engineering of Biocompatible Nanocapsules for Near‐Infrared‐Triggered Drug Release and Photothermal Therapy - Yuting Xie; Ze Yang; Hang Shen; Jingyi Chen; David A. Weitz; Dong Chen; Jianpeng Sheng; Tingbo Liang (Advanced Science, 2025)
Abstract Chemotherapy is an effective option for cancer treatment. However, its clinical application is often limited by the severe side effects of chemical drugs. To overcome these limitations, a novel drug‐loaded phase‐change nanocapsule system is developed. These nanocapsules are assembled via one‐step electrostatic self‐assembly through guided interfacial engineering. The phase change material core nanocapsules demonstrate great photothermal‐controlled drug release performance and exhibit excellent tumor‐targeting drug delivery performance both in vitro and in vivo via the binding of hyaluronic acid shell on the nanocapsule surface with corresponding receptors on the tumor cell membrane. The phototherapy function of the nanocapsules enhances immune activation within the tumor microenvironment, as demonstrated by flow cytometry and multiplex immunohistochemistry. The developed nanocapsules are biocompatible, versatile, and scalable and offer a promising smart delivery platform for controllable near‐infrared triggered drug release and photothermal therapy.